2011
DOI: 10.1063/1.3563577
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of combustion instability in a lean premixed gas-turbine combustor

Abstract: We experimentally investigate the dynamic behavior of the combustion instability in a lean premixed gas-turbine combustor from the viewpoint of nonlinear dynamics. A nonlinear time series analysis in combination with a surrogate data method clearly reveals that as the equivalence ratio increases, the dynamic behavior of the combustion instability undergoes a significant transition from stochastic fluctuation to periodic oscillation through low-dimensional chaotic oscillation. We also show that a nonlinear fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 43 publications
1
117
0
Order By: Relevance
“…These solutions have multiple local peaks at each value of the control parameter R. These types of solution appear in thermoacoustic models such as Figs. 4 and 6 in Sterling and Zukoski [5 and in thermoacoustic experiments such as Gotoda et al 55 and Kabiraj et al Non-normality and transient growth…”
Section: Nonlinearity and Bifurcation Diagramsmentioning
confidence: 99%
“…These solutions have multiple local peaks at each value of the control parameter R. These types of solution appear in thermoacoustic models such as Figs. 4 and 6 in Sterling and Zukoski [5 and in thermoacoustic experiments such as Gotoda et al 55 and Kabiraj et al Non-normality and transient growth…”
Section: Nonlinearity and Bifurcation Diagramsmentioning
confidence: 99%
“…However, a major drawback is the bifurcation in the combustor behavior at the frequency break-point; therefore, it may not be used as a tool of early warning, thus motivating the need for a fast predictive tool that is generic. Both analytical and experimental investigations on the onset of thermo-acoustic instabilities have been reported by several researchers, for example, Lieuwen, 12 Gotoda et al, 13,14 and Murugesan and Sujith. 15 Some of these recent studies have shown the possibility of encountering low-dimensional chaotic oscillations in combustors by employing several methods of nonlinear time series analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of nonlinear oscillations have been found in combustion systems in addition to the normally observed stable limit cycles, with even chaos occasionally taking place [6][7][8]. In a duct burner with a laminar premixed flame, Kabiraj et al [6] observed quasi-periodic, aperiodic and chaotic oscillations when varying the flame location in the duct.…”
Section: Introductionmentioning
confidence: 99%